Analysis of Millennial Tourists’ Interests in Garut Regency - Hanna Daniati; M. Agus Syadad; Ridwan Iskandar; Roselinawati; Ignatius Purwanggono (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2021)
Millennials are highly potential for being targeted as tourists in Garut Regency. This quantitative study, therefore, was aimed at analyzing the interests of millennial tourists in Garut Regency. The results found that the millennial tourists’ interest in Garut Regency with the highest value is the socioeconomically introverted. This shows that even though considered as young tourists and having high productivity, the millenn ial tourists, in conducting tourism activities, are still influenced by the desire to refresh, have fun, socialize, and take advantage of their spare time.